Investigating Endosulfan Consequences: Resistance, Immunology, and Teratogenic Manifestations in Layers and Their Offspring - Manju bargavi SK, Preeti Naval, Savita Yadav (Revista Electronica de Veterinaria, 2024)
Endosulfan, a common organochlorine pesticide, has recently been focus of significant research owing to its negative effects on the surroundings and on living species. The study aimed to assess to immunological effects of limited oral administration of endosulfan insecticide in white leghorn layer chickens. Twenty white leghorn birds were given endosulfan in drinking water at a dosage of 40 ppm/bird/day for three months, which is a detectable effect level dose. Immunological competence was evaluated in layer birds every 16 days and in chicks hatched from endosulfan-exposed birds on a monthly basis. Various immunological, biochemical, and teratological parameters were measured. The study recognizes the significant of investigating endosulfanuses an ANOVA test to resistance, immunology, and their offspring. The white leghorn bird dataset are collected. The quantity of oxalate in eggs improved considerably for both the White Leghorn (p0.07) and Dwarf Layer (p0.004) species after Marigold Flower Extract (MFE), rising to 212.60 μg/egg and 166.80 μg/egg, respectively. The breeds fed the Control (CON) and an MFE diet was not able to exhibit significant variations in the quantity of carotenoid in their eggs.The goal of this research is to clarify the complex effect of endosulfan exposure on both layers and their offspring to inform health and environmental policy.Tests for immune competence, such as the enzyme linked immunosorbent assay (ELISA) and the lymph cell stimulating test indicated that endosulfan treated birds showed decreased immunity. Interestingly, to significant differences were observed inthe avian endosulfan treatment’s effect on the immunological competence of the offspring as compared to the control group. The study suggests that limited oral exposure to endosulfan induces hemo biochemical changes associated with alterations in the immunological profile of layer chickens. The results therefore support the use of endosulfan insecticide in chicken sheds selectively to reduce any effects on the immune system.